1965
DOI: 10.1139/v65-319
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Sugar Chlorosulfates: Part V. The Synthesis of Chlorodeoxy Sugars

Abstract: The reaction of sulfuryl chloride with reducing sugars and their methyl glycopyranosides was shown to produce fully substituted pyranose derivatives containing both chlorodeoxy and chlorosulfate ester groups. I t was demonstrated that the chlorodeoxy groups were formed by llucleophilic displacement ( S N~) by chloride ion of specific reactive chlorosulfate groups in fully chlorosulfated intermediates. The degree of chloro-substitution was shown to be determined by both steric and electronic effects in the indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

1966
1966
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(25 citation statements)
references
References 13 publications
1
23
0
1
Order By: Relevance
“…The syrup above was dechlorosulfated with sodium iodide in aqueous-acetone in the presence of barium carbonate (16). The solution was filtered free of insoluble salts and deionized by passage through Amberlite 1R120 and Duolite A4 ion-exchange resins.…”
Section: Methodsmentioning
confidence: 99%
“…The syrup above was dechlorosulfated with sodium iodide in aqueous-acetone in the presence of barium carbonate (16). The solution was filtered free of insoluble salts and deionized by passage through Amberlite 1R120 and Duolite A4 ion-exchange resins.…”
Section: Methodsmentioning
confidence: 99%
“…La rtaction du chlorure de sulfuryle sur les sucres rtducteurs, A basse temptrature, conduit dans les conditions d'isolement dtcrites par Jennings et Jones (1,2) A des trichloro-1,4,6 tridtsoxy-1,4,6 dichlorosulfate-2,3 hexopyrannose pour les hexopyrannoses et 2 des dichloro-1,4 dichlorosulfate-2,3 pentopyrannose pour les pentoses. Par modification des conditions d'isolement, Jennings dtcrit ~~lttrieurement (3-5) la preparation de chloro-1 trichlorosulfate-2,3,4 pentopyrannose.…”
Section: Introductionunclassified
“…Elemental analysis showed the formation of a dichlorodideoxy compound, and periodate oxidation results indicated that the chlorodeoxy groups were a t the C-3 and C-6 positions. The D-all0 configuratioil is assumed, since in all cases examined hitherto the chlorodeoxy groups were observed to be introduced with inversion (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%